PENGEMBANGAN MEDIA FLIPBOOK INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP VEKTOR SISWA KELAS XI SMA - Sinar, Yunitasia; Kaleka, Melkyanus Bili Umbu; Nasar, Adrianus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research aims(1) To determine the validity of flipbook learning media as a tool for learning physics in vectors. (2) To determine the practicality of flipbook learning media as a tool for learning physics in vectors. (3) To determine the effectiveness of flipbook learning media as a tool for learning physics in vectors.The type of research used is Research and Development with ADDIE (Analysis, Design, Development, Implementation, Evaluation) design. The research subjects were 4 validator trials consisting of two lecturers as media experts and 2 physics subject teachers as material experts, as well as 36 students of SMA Negeri 1 Ende. Data collection was carried out using questionnaires and test techniques. The results of the study showed that the assessment by material experts was categorized as very valid (88%), the assessment by media experts was categorized as very valid (92%), the assessment by participants through a practicality questionnaire was categorized as very practical (96%), and the assessment of student learning outcomes through pretests and posttests was categorized as high (0.76). This shows that the flipbook learning media is valid, practical, and effective to use.